Tumor-derived factors affecting immune cells. (August 2017) - Russo, Vincenzo; Protti, Maria Pia
Abstract: Tumor progression is accompanied by the production of a wide array of immunosuppressive factors by tumor and non-tumor cells forming the tumor microenvironment. These factors belonging to cytokines, growth factors, metabolites, glycan-binding proteins and glycoproteins are responsible for the establishment of immunosuppressive networks leading towards tumor promotion, invasion and metastasis. In pre-clinical tumor models, the inactivation of some of these suppressive networks reprograms the phenotypic and functional features of tumor-infiltrating immune cells, ultimately favoring effective anti-tumor immune responses. We will discuss factors and mechanisms identified in both mouse and human tumors, and the possibility to associate drugs inhibiting these mechanisms with new immunotherapy strategies already entered in the clinical practice.